Inhibitory Effects of Sigma-2 Receptor Agonists on T Lymphocyte Activation - Iñiguez, Miguel A.; Punzón, Carmen; Nieto, Raquel; Burgueño, Javier; Vela, José M.; FRESNO, MANUEL (Frontiers in Pharmacology, 2013)
Sigma (σ) receptor ligands are essentially known for their effects on the nervous system although recent studies have shown their potential effects modulating some other pathophysiological processes as cell proliferation, cancer and the immune response. Here, we have analyzed the actions of σ-1 and σ-2 receptors ligands on T cell activation. Our results show that treatment of Jurkat T cells with σ-2 agonists decreased the induction of the expression of Interleukin (IL)-2, Tumor necrosis factor (TNF)-α and Cyclooxygenase (COX)-2 by activated T cells in a dose–dependent manner. These effects take place at the transcriptional level since σ-2 agonists BD-737 and CB-184 diminished the activity of the promoters of those genes. Those immunosuppressive effects could be attributable to interference with transcription factor activation. Induced transcription mediated by Nuclear factor (NF)-κB or Nuclear Factor of Activated T cells (NFAT) was inhibited by σ-2 agonists. These effects seem to be specific for σ-2 agonists as no significant effects on T cell activation by σ-1 ligands PRE-084 and BD-1063 were found. Our results provide new insights into the immunomodulatory actions of σ ligands and describe a new property of σ-2 agonists, through inhibition of activation of transcription factors as NFAT by which these compounds are regulating gene expression. This may have important consequences on the possible therapeutic use of those compounds.